EFFECT OF EUCALYPTUS LEAVES AND ITS SUPPLEMENTATION WITH DIET ON BROILER PERFORMANCE, MICROBIAL AND PHYSIOLOGICAL STATUES TO ALLEVIATE COLD STRESS - AG. Mustafa, M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this study was to investigate the effects of Eucalyptus Camaldulensis leaves powder (EUP) and oil (EUO) to alleviate cold stress and their effects on broiler performance, duodenum morphology and enzyme secretion, microbial counts, oxidative index expression levels of heat shock protein, vitamin E and TBARS (thiobarbituric acid-reactive substances) and meat sensory evaluation. Six hundred thirty-one day-old unsexed  chicks were randomly divided into 7 groups: control (basal diet), EuP (0.5, 1, & 2) %, EuO (0.05, 0.1 & 0.2) %, the chicks kept under the temperature of 17°C afternoon and 15°C at night for under cold stress condition.The results of dietary addition with Eucalyptus powder-EuP (1.0) % or (EuO) oil (0.05, 0.1 and 0.2) % were significantly (p≤0.05) higher in body weight (BW), body weight gain (BWG), economic profit (EP), small intestine relative length, duodenum (more number of goblet cells, villus height, crypt depth, improved the secretion of amylase, lipase, trypsin and chymotrypsin, total count of Lactobacillus), blood vitamin E, the thigh and breast meat sensory evaluation (juiciness and flavor). While, decreased broiler mortality, duodenum: (pH acidity. E. Coli, Coliforms perfringens and Salmonella typhimurium) blood TBARS concentration, Heat shock protein (Hsp: 40, 70 and 90), less hardness and TBARS in the thigh and breast of broiler meat compared with the control. In the most characteristics the age 35 d superiority 42 d.